Relationships of collaboration and power between specialist teachers and mainstream teachers in inclusive schools - Gouttefarde, Amandine (Swiss Journal of Educational Research, 2023)
This article proposes a theorization of the collaborative relationship between mainstream and special education teachers. Our results show that inclusive policies place special education teachers in an ambiguous professional norm: participatory reserve. To support pupils with special needs, they seek to influence mainstream education teachers’ practices, leading them to seek two forms of power. However, mainstream education teachers exert a counter-power effect in addition to the norms of convivialism, benevolent neutrality and caring attitude.